Peran Kepemimpinan Kepala Sekolah dalam Meningkatkan Kualitas Sumber Daya Manusia di MI/SD - Diyah Andini Kusumastuti; Alisia Zahro’atul Baroroh; Ahmad Ta’rifin; Elis Nursetialloh (Lembaga Pengembangan Kinerja Dosen, 2026)
The quality of human resources (HR) in Islamic and public primary schools (MI/SD) is a key factor in improving the quality of basic education and is strongly influenced by the leadership role of the school principal. Principals function not only as administrators but also as instructional leaders who are capable of mobilizing teachers and educational staff to develop professionally. This study aims to analyze the role of school principal leadership in improving the quality of human resources in MI/SD, particularly in terms of pedagogical, professional, social, and personal competencies of teachers and educational staff. This research employed a qualitative approach using a case study method. Data were collected through in-depth interviews, observations, and documentation studies, while data analysis was conducted through data reduction, data display, and conclusion drawing. The findings indicate that visionary, participatory, and transformational leadership of school principals plays a significant role in enhancing the quality of human resources. Principals actively encourage teacher professional development through academic supervision, continuous training, teamwork empowerment, and the creation of a supportive and collaborative school culture. In addition, the principal’s exemplary behavior in discipline, communication, and decision-making contributes positively to increasing motivation and performance among teachers and staff. The implications of this study suggest that improving the quality of basic education in MI/SD requires strengthening school principals’ leadership competencies so that they are able to manage and develop human resources in a sustainable manner and oriented toward educational quality improvement.